On the nature of Scleropages leichardti Günther, 1864 (Pisces: Osteoglossidae) - Pusey, Bradley J.; Fisher, Clemency; Maclaine, James (Zootaxa, 2016)
The Australasian Saratoga (Pisces: Osteoglossidae) is currently recognised as comprised of two species Scleropages leichardti and S. jardinii. The Prussian explorer Ludwig Leichhardt (1813–c.1848) collected specimens of both species on his first major expedition across northern Australia but believed at the time that all specimens collected were from within one species. Details of the fate of these specimens are unclear as is the geographic origin of those specimens that ultimately made their way into museum collections. Günther’s 1864 description of the Southern Saratoga S. leichardti, purportedly from the Fitzroy River in Queensland to which it is restricted (although he erred and listed it as the Burdekin River) is meagre and inconsistent with contemporary accounts of the morphology of this species. It is also inconsistent with a subsequent description by de Castelnau in 1876 of the supposedly synonymous Osteoglossum guntheri. Finally, the description of S. leichardti by Günther is largely consistent with meristic and morphometric information within Saville-Kent’s (1892) description of the wide-spread Northern Saratoga S. jardinii. On balance, these inconsistencies, doubt about the provenance and geographic origin of type material and provenance of the original descriptions all strongly suggest that Günther based his description of S. leichardti on material collected from within the range of the more widespread taxon currently recognised as S. jardinii. A revision of the Australian species within the genus Scleropages is warranted.